MENINGKATKAN KOOPERATIF SELAMA MENJALANI PERAWATAN PADA ANAK USIA PRASEKOLAH (3-5 TAHUN) MELALUI TERAPI BERMAIN - Hasnita, Evi (Jurnal Ilmiah Keperawatan, 2018)
A total of 45 % child was hospitalized are not cooperative during has hospitalisasi. Play therapy can reduce fear, anxiety and stress and to improve the cooperative child. The aim of this study was to determine the influence play therapy on the level of cooperative preschool children (3-5 years) during hospitalized. This research is Quasi Eksperimen with One Group Pretest – Postest Design. The population is all children aged 3-5 years amounted to 43 people and sample in this research are 10 respondents taken by purposive sampling technique. The result showed the average level cooperative before play therapy is 21.02. While the average level cooperative after play therapy is 24.94. The statistical test result shows was the influence play therapy on the level of cooperative preschool children (3-5 years) during hospitalized with p value 0.001. It can be concluded that improving cooperative during hospitalized on children (3-5 years) by play therapy. Expected to nursing practice, so that the results of this research can be applied in nursing services to children due to hospitalization. Subsequent studies that examined the various groups play in the knowing cooperation. Keywords : Cooperative Child, Hospitalization, Play Therapy